Improving Phosphate-Solubilizing Rhizobacteria Strains via Mutation to Enhance Phosphorus Availability in Acidic Soils - Adin Heriyan Nugroho; Faizzah Kahfi Putri; Hamda Hamidatu Sya'diyah; Aprilia Fatmawati; Hafidho Muntazul Ghiffar; Eka Oktaviani (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2026)
Acid-dry land is a suboptimal land area widely distributed in Indonesia, which has the potential to be developed as cropland to increase crop productivity. However, the low phosphorus availability in this land type often constrains plant growth, necessitating the use of microbial phosphate-solubilizing agents. To address this, the capability of the isolated rhizobacteria strain in phosphate solubilization was improved through a mutagenesis by Ethyl Methane Sulphonate (EMS). Three isolates of indigenous wild-type rhizobacteria of acid-dry land were isolated from cardamom, lemon grass, and bamboo rhizosphere. Mutagenesis of these wild-types yielded three mutant isolates, including KPG_m, SRH_m, and BMB_m, which exhibited higher Phosphate-Solubilization Indices (PSI) compared to their parental strains. The PSI values for the mutants were 2.2, 3.4, and 2.0, respectively, showing a marked improvement over the wild-type values of 2.0, 1.75, and 1.25. These results indicate an enhancement in phosphate-solubilizing ability driven by EMS mutagenesis. All the isolates were then characterized and showed similar traits to those of the Genus of Bacillus. According to the hypersensitive reaction assay, the six isolates showed a negative reaction, indicating they are non-pathogenic. Based on these findings, the mutants have the potential to be developed as biofertilizer agents due to they are non-pathogenic for plants. In addition, the mutants have a moderate PSI value (2<PSI<4) and effective solubilization rate that may improve phosphate solubilization process in acid-dry land.